2018
DOI: 10.3390/geosciences8040110
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Growth of Flexural Slip Fault-Bend and Fault-Propagation Folds and Their Geomorphic Expression

Abstract: Abstract:The three-dimensional growth of fault-related folds is known to be an important process during the development of compressive mountain belts. However, comparatively little is known concerning the manner in which fold growth is expressed in topographic relief and local drainage networks. Here we report results from a coupled kinematic and surface process model of fault-related folding. We consider flexural slip fault-bend and fault-propagation folds that grow in both the transport and strike directions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 113 publications
(192 reference statements)
0
1
0
Order By: Relevance
“…Since the pioneering research of Shelton (1966), many field studies have used geomorphic criteria to evaluate the direction and rates of lateral propagation of active structures. In a general manner, the asymmetry of drainage networks, lateral deflection of rivers, and/or the existence of wind or water gaps have been considered as evidence of lateral fold propagation (e.g., Bernal et al, 2018;Bretis et al, 2011;Delcaillau et al, 1998;Jackson et al, 1996;Keller et al, 1999;Mueller & Talling, 1997;Ramsey et al, 2008). Similarly, several studies have observed alongstrike variations in the timing and amount of deformation of geomorphic surfaces and interpreted these differences as caused by lateral fault growth and fold propagation (e.g., Benedetti et al, 2000;Bennett et al, 2005;Jackson et al, 2002;Hetzel et al, 2004;Li et al, 2013;Keller et al, 1999;Morewood & Roberts, 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering research of Shelton (1966), many field studies have used geomorphic criteria to evaluate the direction and rates of lateral propagation of active structures. In a general manner, the asymmetry of drainage networks, lateral deflection of rivers, and/or the existence of wind or water gaps have been considered as evidence of lateral fold propagation (e.g., Bernal et al, 2018;Bretis et al, 2011;Delcaillau et al, 1998;Jackson et al, 1996;Keller et al, 1999;Mueller & Talling, 1997;Ramsey et al, 2008). Similarly, several studies have observed alongstrike variations in the timing and amount of deformation of geomorphic surfaces and interpreted these differences as caused by lateral fault growth and fold propagation (e.g., Benedetti et al, 2000;Bennett et al, 2005;Jackson et al, 2002;Hetzel et al, 2004;Li et al, 2013;Keller et al, 1999;Morewood & Roberts, 1999.…”
Section: Introductionmentioning
confidence: 99%